PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL PADA PERANGKAT DAERAH DI KABUPATEN MALUKU TENGGARA - Gufra Zilhalim Rahawarin, (Journal of Innovation Research and Knowledge, 2026)
This research aims to examine the effect of organizational commitment on managerial performance in The Local Bureaucracy in Southeast Maluku Regency. This study uses a quantitative approach. The population in this study were three people from each The Local Bureaucracy within the Southeast Maluku Regency Government. The sample was determined using the census method and obtained 123 respondents. The research results show organizational commitment has a positive and significant effect on managerial performance in The Local Bureaucracy in Southeast Maluku Regency.